Enhanced surveillance for adverse events following immunization during the 2019 typhoid conjugate vaccine campaign in Harare, Zimbabwe. Issue 26 (9th June 2022) - Shaum, Anna; Mujuru, Hilda A.; Takamiya, Mayuko; Ticklay, Ismail; Nathoo, Kusum; Sreenivasan, Nandini; Nyambayo, Priscilla; Chitando, Phillomina; Marembo, Joan; Koline Chigodo, Colline; Mukaratirwa, Arnold; Jacha, Vengai; et al.
Highlights: Safety evaluation of TCV in first use in Africa outside of clinical trials. Hospital surveillance enhanced passive monitoring; results support safety of TCV. More work on background rates of AEFI conditions in low resource settings needed. Abstract: Background: During February 25–March 4, 2019, Zimbabwe's Ministry of Health and Child Care conducted an emergency campaign using 342, 000 doses of typhoid conjugate vaccine (TCV) targeting individuals 6 months–15 years of age in eight high-risk suburbs of Harare and up to 45 years of age in one suburb of Harare. The campaign represented the first use of TCV in Africa outside of clinical trials. Methods: Three methods were used to capture adverse events during the campaign and for 42 days following the last dose administered: (1) active surveillance in two Harare hospitals, (2) national passive surveillance, and (3) a post-campaign coverage survey. Results: Thirty-nine adverse events were identified during active surveillance, including 19 seizure cases (16 were febrile), 16 hypersensitivity cases, 1 thrombocytopenia case, 1 anaphylaxis case, and two cases with two conditions. Only 21 (54%) of 39 patients were hospitalized and 38 recovered without sequelae. Attack rates per 100, 000 TCV doses administered were highest for seizures (6.27) and hypersensitivity (5.02). Only 6 adverse events were reported through passive surveillance by facilities other than the two active surveillance hospitals. A total of 177 (10%) of 1, 817 vaccinees surveyed reported experiencing an adverse event during the post-campaign coverage survey, of which 25 (14%) sought care. Conclusions: In line with previous evaluations of TCV, enhanced adverse event monitoring during an emergency campaign supports the safety of TCV. The majority of reported events were minor or resulted in recovery without long-term sequelae. Attack rates for seizures and hypersensitivity were low compared with previous active surveillance studies conducted in Kenya and Burkina Faso. Strengthening adverse event monitoring in Zimbabwe and establishing background rates of conditions of interest in the general population may improve future safety monitoring during new vaccine introductions.